Cobas® 4800 HPV test is accurate for detecting high risk Human Papillomavirus from urine samples at dr. Cipto Mangunkusumo National Central General Hospital, Jakarta, Indonesia - Wityawan, Indiarto; Andrijono; Kekalih, Aria (Majalah Obstetri & Ginekologi, 2022)
HIGHLIGHTS 1. The presence of Human Papillomavirus (HPV) can be detected using urine samples, as compared to cervical samples, by means of Cobas® 4800 HPV test. 2. The concordance between cervical and urine samples for HPV DNA was found as much as 84.72%. 3. Urine samples subjected to Cobas® 4800 HPV test is helpful to treat HPV infection. ABSTRACT Objective: To find the accuracy, sensitivity, specificity, as well as predicted values, both positive and negative, of urine samples using Cobas® 4800 in detecting high risk Human Papillomavirus. Materials and Methods: This study was a cross-sectional study with a total of 72 samples taken from medical records of hrHPV DNA examination with Cobas® 4800 in 2017-2020. Study subjects were called for re-examination of urine samples and cervical samples using Cobas® 4800. Samples with positive hrHPV DNA in the cervix, urine, or both were examined for cervical fluid-based cytology (LBC). Data were analyzed using Chi-square. Results: Overall, 84.72% agreement was detected through specimens of urine and cervical mucus tested of hrHPV DNA with Cobas® 4800. In all samples, a significant rate of concordance detection of hrHPV DNA with Cobas® 4800 was reported (ka = 0.62; 95% IC: 39-84). In this population, in determining the presence of hrHPV DNA in cervical and urine specimens, it was found that the sensitivity, specificity, positive predictive value and negative predictive value were respectively 87.5% (95% IC: 64–97%), 84% (95% IC: 72–91%), 60.9% (95% IC: 40.8–77.8%), and 96 % (95% IC: 86.3–98.9%). Conclusion: The presence of hrHPV infection in the cervix can be determined by detecting hrHPV DNA in the urine. According to these findings, urine samples subjected to the Cobas® 4800 HPV test may be helpful for the clinical treatment of HPV infection.